Adverse selection analysis for profit and loss sharing contracts - Ajmi, Hechem; Abd Aziz, Hassanuddeen; Kassim, Salina; Mansour, Walid (Emerald Publishing, 2019)
Purpose – The purpose of this paper is to determine the optimal profit-and-loss sharing (PLS)-based contract when market frictions occur.